آليات التّّماسك النّّصيّ في القرآن الكريم (السّيوطيّ وابْن هشام الأنْصاريّ أنْْموذجان) - موساوي عبد العالي (University of Eloued جامعة الوادي, 2023)
التماسك النّصّي اتّجاه حديث في دراسة النّص ، تبَلْورتْ ماهيّته وأسُسه في الغرب ، والورقة التي بين أيْدينا توثّق الأُسُس بيْن علماء اللّغة العَرب (التّراث) والغرْب ،كما تكشف عن وظيفة هذا الاتجاه وغايته؛ محاولة لفْت نظر الدّارسين إلى كيفيّة اسْتثماره في تحْليلاتهم اللّسانيّة, فكان العنوان: آليات التّّماسك النّّصيّ (السّيوطي وابْن هشام الأنْصاري أنْموذجان) . ويتلخّص البحثُ في الإجابة على سؤالٍ عامٍّ هو: كيْف يظْهر التّماسُك النّصِي منْ خِلالِ الجُهود اللّغَويّة للسّيوطي وابْن هِشام الأنْصارِيّ؟ ولمعالجة ذلك بنيْنا المقال على: مقدّمة حُرّر فيها الاشكال والغاية من الموْضوع ، ثم عرْض يتمثّل في حُدود الدّراسات اللّغويّة : الجُملة والنّص والتّركيز علَى التّماسُك النّصي و ما يتعلّق بأسسه ولم نغْفِل ما توصّل إليْه علماء الغرب . ثم إبراز جهود العرب - السّيوطي وابنْ هشام الأنصاريّ – في تحْليلهم وتفْسيرهم للنّص القرآنيّ، و خاتمةٍ جمَعتْ نتائج دلّتْ على سبْق العرب في الدّراسات النّصيّة ؛ و جُهودهم التي تميّزتْ بالجِدّة والدّقة و اسْتنتاج الآليات التي أظهرتْ إحْكام آيات القرآن واتّساقها. Textual cohesion is a recent trend in the study of text, its nature and foundations crystallized in the West, and the paper in our hands documents the foundations between Arab linguists (the heritage) and the West, and also reveals the function and purpose of this trend; An attempt to draw the attention of scholars to how to invest it in their linguistic analyses, so the title was: Mechanisms of Textual Cohesion (Al-Suyuti and Ibn Hisham Al-Ansari as two models). The research is summed up in answering a general question: How does textual cohesion appear through the linguistic efforts of Al-Suyuti and his son? Sham Al-Ansari? To address this, we built the article on: an introduction in which the forms and purpose of the topic were highlighted, then a presentation representing the limits of linguistic studies: the sentence and the text, focusing on textual cohesion and what relates to its foundations, and we did not ignore what Western scholars have reached. Then highlighting the efforts of the Arabs - Al-Suyuti and Ibn Hisham Al-Ansari - in their analysis and interpretation of the Qur’anic text, and a conclusion that collected results that indicated the Arabs’ precedence in textual studies. Their efforts were characterized by novelty, accuracy, and deduction of mechanisms that demonstrated the precision and consistency of the verses of the Qur’an.
Mechanisms Of Textual Cohesion In The Holy Qur’an (al-suyuti And Ibn Hisham Al-ansari Are Two Models
Keywords: التماسك النّصي; لسانيات الجُملة; لسانيات النّص; الجُملة; النّص; textual cohesion; sentence linguistics; text linguistics; sentence; text.